Development of a Test Bench for Fault Diagnosis in the Caution and Warning Panels of the UH-60 Helicopter - Cristian Sáenz-Hernández; Rubén Cuadros; Jorge Rodríguez; Edwin Rativa; Mario Linares-Vásquez; Yezid Donoso; Cristian Lozano (Eng)
This article presents the development and implementation of an automated digital test bench for fault diagnosis in the caution and warning panels of the UH-60 helicopter, using practices based on NASA’s systems engineering process. The research addresses the critical need to improve efficiency and accuracy in aeronautical maintenance by automating processes traditionally relying on manual techniques. Throughout the study, advanced software engineering methodologies were implemented to develop a system that significantly reduces diagnostic times and enhances the accuracy and reliability of results by integrating digital signal processing. The article highlights the economic benefits, demonstrating a substantial reduction in repair costs, and emphasizes the system’s flexibility to adapt to other aeronautical components, establishing a solid foundation for future technological innovations in aircraft maintenance. The novelty of this paper lies in integrating real-time simulation with a closed-loop diagnostic system designed primarily for the UH-60 avionics panels. This approach has not previously been applied to this series of aircraft or aeronautical components, allowing for adaptive and automated fault detection and significant improvement in diagnostic accuracy and speed in unscheduled aeronautical maintenance environments.